PERBEDAAN PENGUASAAN KONSEP IKATAN KIMIA PEMBELAJARAN KOOPERATIF NHT DENGAN PEMBELAJARAN KOOPERATIF TPS - Rina Meri M; Ila Rosilawati; Tasviri Efkar (Universitas Lampung, 2013)
The purpose of this study is whether there is any difference between the value of student’s mastery of the concept of NHT cooperative learning with TPS cooperative learning and determine the average value of student’s concept which is higher between NHT cooperative learning with TPS cooperative learning in the chemical bonds matery. The samples in this research were the student’s of SMA Tri Sukses Natar class X 3 and X5 in academic year 2012/2013. The design of this study is using the Matching -Only Group Posttest -Only Design. The results showed that; there is a difference in the student’s mastery of the chemical bond mastery between the matery given by the NHT cooperative learning with TPS cooperative learning and the average value of student concept mastery of chemical bonds in the matery using TPS cooperative learning TPS higher than with NHT cooperative learning.Tujuan penelitian ini adalah ada tidaknya perbedaan nilai penguasaan konsep siswa antara pembelajaran kooperatif NHT dengan pembelajaran kooperatif TPS dan menentukan nilai rata-rata penguasaan konsep siswa yang lebih tinggi antara pembelajaran kooperatif NHT dengan kooperatif TPS pada materi ikatan kimia. Sampel dalam penelitian ini adalah siswa SMA Tri Sukses Natar kelas X3 dan X5 tahun pelajaran 2012/2013. Desain penelitian ini menggunakan The Matching-Only Posttest-Only Group Design. Hasil penelitian menunjukkan ada perbedaan penguasaan konsep siswa pada materi ikatan kimia antara yang diberi pembelajaran kooperatif NHT dengan pembelajaran kooperatif TPS; dan nilai rata-ratapenguasaan konsep siswa pada materi ikatan kimia dengan menggunakan pembelajaran kooperatif TPS lebih tinggi dari pada pembelajaran kooperatif tipe NHT. Kata kunci: NHT, penguasaan konsep, TPS